Pecan Production, Exporting, and Its Future: From a Multi-Country Perspective - Nadler, Scott; Chen, Alexander N; Lu, Hsin-Ke (Journal of Applied Business and Economics, 2017)
The pecan industry, which is dominated by the United States, plays an important role in the multi-billion dollar worldwide tree nut industry. Pecans are currently produced in commercial quantities in countries as diverse as the US, Australia, Mexico, Israel, South Africa, Vietnam and China among others. However, few academic studies have investigated this important agricultural commodity from other than a production perspective. This study contributes to the agricultural, economic, international trade and business literature by providing a review of the current state of the pecan industry in China and its potential for future growth. This study also represents a significant departure from past research in that it is among the first to review both the US and Chinese literature bases.